A modified constrained constant modulus approach to blind adaptive multiuser detection. - Changjiang Xu
An alternative blind adaptive multiuser detection is investigated based on modified constrained constant modulus (CM) criterion. It is shown that the performance of a CM-based receiver is limited by the received power of the desired user. In this paper, we show that the limitation can be avoided using the noncanonical constraint CM criterion and that in the presence of channel noise the modified CM criterion function is strictly convex by properly selecting some constant. With analyzing the extrema of the cost function, we point out how to select the constant. Moreover, a simple stochastic gradient algorithm for implementing our scheme is presented, and the convergence properties of the algorithm are analyzed. Simulation examples are given to demonstrate the performance of the proposed scheme
Keywords: CM-based receiver; Blind adaptive multiuser detection; Channel noise; Convergence properties; Cost function; Desired user; Modified constrained constant modulus approach; Noncanonical constraint CM criterion; Performance; Received power; Stochastic gradient algorithm